Application of Micro Hydro Power to Improve Community Welfare by Utilizing Alternative Energy in Remote Areas - Suripto, Heri; Anwar, Saiful; Subekti, Purwo (International Conference on Sciences Development and Technology, 2022)
Remote areas with access to steep roads and hills present challenges for the government’s establishment of power plants, but these can be overcome by utilizing alternative energy sources available in the area, such as wind, solar, and hydro energy. In this study, we will develop a research-based hydro energy source that has been tested on a micro scale at Pasir Pengaraian University laboratory. The community-based research approach is used to meet the objectives' requirements, such as survey activities, planning, analysis, and application of the agreed-upon technology. Alternative hydro energy must be developed further to improve net-zero energy systems. As a result of this activity, the community no longer complains about electrical energy; rather, they can convert alternative energy sources into hydroelectric energy as a backup. The study's results show that a wheel with a diameter of 120 cm, a width of 40 cm, and 18 pcs of blades is able to generate 850 watts of energy with a gear and chain transmission ratio. This study allows the village to become energy independent and has the potential to improve welfare through the application of appropriate technology. It is hoped that by using this technology, the village will be able to generate their own electricity through mentorship activities